PERBEDAAN NILAI ASIMETRI INFORMASI PADA ASSURANCE DAN NON ASSURANCE SUSTAINABILITY REPORT - Ani Purwati; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2019)
Sustainability reporting has evolved over the past decade. Corporate reporting is made for use by various interested parties, namely internal parties and external parties. When company information owned by management (internal parties) is more than stakeholders (external parties) there will be information asymmetry. Guarantees or assurance in sustainability reports are needed to increase confidence in the accuracy of the information reported by the company, so that the information asymmetry will be lower. This study aims to determine whether the information asymmetry in the non assurance sustainability report is greater than the sustainability assurance report.Forecast error analysis as a proxy to represent information asymmetry (Cuadrado-Ballesteros, 2013). This study uses a non-parametric test, namely Wilcoxon Mann Whitney test, because the data do not meet the prerequisites for hypothesis testing, namely differences in median, normality test, and homogeneity test.The testing of the null hypothesis using Wilcoxon Mann Whitney test showed that the asymmetry of information in the Sustainability Report that did not have assurance (not guaranteed) was greater than the Sustainability Report which had assurance.